FORMATION OF PROFESSIONAL AND PERSONAL QUALITIES OF STUDENTS IN THE PROCESS OF THEIR PHYSICAL EDUCATION - I. Tarasenko; M. Malashenko; T. Prokopenko; I. Taran; A. Kudrya (Вестник Северо-Кавказского федерального университета)
The article is sanctified to research of forming mechanism professionally - personality development and self-development ofstudent young people in the process of their P.E in higher educational establishments. This process is speciic self-development of the personality educational and developing space in that he come forward the subject of the professional becoming and self-development of personality. The model of professionally-personality development ofstudent young people is plugged in itself readiness to professional activity, to development and self-development. It is necessary from here, that the process of P.E in institution of higher learning assists the professionally-personality height of student young people with support on the internal sources of self-development, in the situations of comprehension and choice of own personality and professional positions.